2020
DOI: 10.1089/ten.tea.2019.0042
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Tendon Progenitor Cells from Tendinopathic Tendons: Implications for Treatment

Abstract: Tendinopathy remains a significant clinical challenge. Although there is some evidence that leukocyte-rich platelet-rich plasma can improve the symptoms of tendinopathy, more efficacious treatments will be required in the future to improve probability of successfully resolving this condition in athletes. Because optimal treatments are not currently available, there is a need to better understand the pathology of tendinopathy from the perspective of tendon progenitor cells (TPCs). TPCs isolated from normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(61 reference statements)
0
9
0
Order By: Relevance
“… 58 Additionally, another study has reported that despite a higher number of total resident TDPCs in tendinopathic tissue, these TDPCs are unable to differentiate into tenocytes to regulate the extracellular matrix (ECM). 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 Additionally, another study has reported that despite a higher number of total resident TDPCs in tendinopathic tissue, these TDPCs are unable to differentiate into tenocytes to regulate the extracellular matrix (ECM). 5 …”
Section: Discussionmentioning
confidence: 99%
“…58 Additionally, another study has reported that despite a higher number of total resident TDPCs in tendinopathic tissue, these TDPCs are unable to differentiate into tenocytes to regulate the extracellular matrix (ECM). 5 The difficulty in treating tendinopathy lies in the multifactorial pathogenesis of the disease. The utilization of tendon derived stem cells (TDSC) as a biologic agent may address many of these aberrant pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Among different non-exclusive pathogenic mechanisms of tendinopathy, altered fate of stem cells after tendon injury has been suggested as an important pathogenic mechanism [ 16 , 17 ]. The functions of tendon-derived stem/progenitor cells (TDSCs) isolated from tendinopathy patients were altered [ 18 , 19 , 20 ]. More TDSCs, with a lower proliferative capacity and tenogenic potential, but with a higher cellular senescence, non-tenocyte differentiation potential, and inflammatory response, were present in an inflammatory collagenase-induced degenerative failed tendon healing animal model [ 21 , 22 ] and clinical samples of tendinopathy [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of tendon-derived stem/progenitor cells (TDSCs) isolated from tendinopathy patients were altered [ 18 , 19 , 20 ]. More TDSCs, with a lower proliferative capacity and tenogenic potential, but with a higher cellular senescence, non-tenocyte differentiation potential, and inflammatory response, were present in an inflammatory collagenase-induced degenerative failed tendon healing animal model [ 21 , 22 ] and clinical samples of tendinopathy [ 18 , 19 , 20 ]. Tendinopathic TDSCs were unable to differentiate into tenocytes following mechanical stretch [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation